Cover Image, Volume 61, Issue 7. Issue 7 (17th June 2022) - Huang, Shih‐Bo; Rivas, Paul; Yang, Xiaoyu; Lai, Zhao; Chen, Yidong; Schadler, Keri L.; Hu, Ming; Reddick, Robert L.; Ghosh, Rita; Kumar, Addanki P.
Abstract : The cover image is based on the Research Article SIRT1 inhibition‐induced senescence as a strategy to prevent prostate cancer progression by Shih‐Bo Huang et al., https://doi.org/10.1002/mc.23412